Investigando o desempenho isolante e de perdas e dielétricas do molibdato de calcio (CaMoO4), sob adição de TiO2, para aplicações em ressoadores dielétricos - Nogueira, Francisco Enilton Alves (2024)
In this work, the structural and dielectric properties of the CaMoO4 (CMO) ceramic matrix were studied, with mass addition of titanium oxide (TiO2), in proportions of 8, 12, and 20%. The samples were prepared using the solid-state reaction method, followed by calcination at 900 ºC. After calcination, the powders were pressed into cylindrical shape and sintered at 1200 °C. The ceramic pieces obtained were characterized by their structure and morphology by X-ray Diffraction and Scanning Electron Microscopy, respectively. The X-ray Diffraction analysis proves that the CMO matrix was obtained without the presence of spurious phases; in the analysis of the composites, only the CMO and TiO2 crystalline phases were observed. The morphological study and analysis of the micrographs revealed that the addition of TiO2 modified the morphology of the materials, leading to an increase in grains and the appearance of rods of varying sizes. Through the pycnometry test, an improvement in the densification of materials was also observed. Dielectric characterization was carried out in the radio frequency (RF) and microwave (MW) regions. A study of the properties at room temperature and with temperature variation was carried out for possible application in RF and MW devices. The study of ceramics carried out in the MW range suggests that composites from the (CMO)1-x – (TiO2)x series have properties for application as dielectric resonator antenna (DRA). With the results obtained using the Hakki-Coleman method, it was possible to verify that the dielectric permittivity of 9.34 for the pure sample and 19.02 for the addition of 20% TiO2 and dielectric loss tangent in the order of 10- 4 for all samples. The result of the resonance frequency temperature coefficient (τf) showed that with the addition of 8%, it was possible to achieve thermal stability with a value of τf = -5.90 ppm.ºC-1. The antenna parameters were obtained by numerical simulation, where results such as reflection coefficient spectra and antenna impedances showed a good correlation between experimental and simulated results. The gains and efficiencies of the antennas had values such as a realized gain of 2.76 to 3.11 dBi, bandwidth of 741 to 1079 MHz, and a radiation efficiency above 86%. Regarding the results in RF, the values of real permittivity (ε’) and loss tangent (tg δ) at room temperature were analyzed. The Nyquist diagrams were fitted based on an equivalent circuit using two R-CPE associations related to grain and grain boundary effects. The TCC study was also carried out and demonstrated that the CMO12 matrix at 10 KHz presented a TCC value = 0, demonstrating that it is a thermally stable material at this frequency. Studies of the Z”, M” and σ’ spectra with the effect of temperature demonstrate a thermally activated conduction process with an activation energy value (Ea) that varies from 0.85 to 1.41 eV.